2020
DOI: 10.1093/cz/zoaa061
|View full text |Cite
|
Sign up to set email alerts
|

Threat recognition and response in an avian brood-parasite host from New Caledonia

Abstract: Nest predation and avian brood parasitism are the main sources of nest failure in many passerine birds. Large predators threaten both brood and parents, whereas brood parasites pose only a danger to eggs or nestlings. The fan-tailed gerygone Gerygone flavolateralis from New Caledonia is subjected to high rates of nest predation by the New Caledonian crow Corvus moneduloides (responsible for about 20-40% of predation) and moderate rates of brood parasitism by the shining bronze-cuckoo Chalcites lucidus (parasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…All the hosts show some defences at the frontline stage. They react aggressively to adult shining bronze‐cuckoos approaching the nest (Briskie, 2007) as well as to stuffed specimens of shining bronze‐cuckoos presented at the nest (Attisano, Hlebowicz, et al, 2021; Medina & Langmore, 2016). The yellow‐rumped thornbill begins nesting in mid‐winter, substantially earlier than congeneric and sympatric insectivorous species and before migratory cuckoos arrive in their breeding ground, which is consistent with selection for earlier breeding to escape parasitism (Medina & Langmore, 2016).…”
Section: Model Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…All the hosts show some defences at the frontline stage. They react aggressively to adult shining bronze‐cuckoos approaching the nest (Briskie, 2007) as well as to stuffed specimens of shining bronze‐cuckoos presented at the nest (Attisano, Hlebowicz, et al, 2021; Medina & Langmore, 2016). The yellow‐rumped thornbill begins nesting in mid‐winter, substantially earlier than congeneric and sympatric insectivorous species and before migratory cuckoos arrive in their breeding ground, which is consistent with selection for earlier breeding to escape parasitism (Medina & Langmore, 2016).…”
Section: Model Speciesmentioning
confidence: 99%
“…All the hosts show some defences at the frontline stage. They react aggressively to adult shining bronze-cuckoos approaching the nest (Briskie, 2007) as well as to stuffed specimens of shining bronzecuckoos presented at the nest (Attisano, Hlebowicz, et al, 2021; F I G U R E 1 Eggs of shining bronze-cuckoos and their hosts from (a) Australia (cuckoo: olive green; yellow-rumped thornbill: unspotted white; photo by N. Langmore), (b) New Caledonia (cuckoo: dark brown; fan-tailed gerygone: whitish grey with brown speckles; photo by N. Sato) and (c) New Zealand (cuckoo: olive-green; grey warbler: whitish with brown speckles; photo by R. Thorogood). Medina & Langmore, 2016).…”
Section: The Hostsmentioning
confidence: 99%
“… 45 Parasites may also prey on host eggs or chicks, 1 , 46 , 47 , 48 but studies on nest defense have demonstrated that parasites such as common cuckoos are recognized more often by hosts as cues of parasitism than predation. 1 , 49 , 50 , 51 , 52 Field observations suggest that the nest desertion behavior of hosts is primarily triggered by cues of parasitism, suggesting that nest desertion is an important adaptation mechanism of anti-parasitism behavior. 11 , 14 , 53 , 54 While previous studies have investigated host adaptation to nest desertion from different angles, they have rarely examined the impact of parental investment trade-offs on nest desertion at different stages of egg-laying.…”
Section: Introductionmentioning
confidence: 99%